2001
DOI: 10.1136/jnnp.70.5.644
|View full text |Cite
|
Sign up to set email alerts
|

Reconsideration of biallelic inactivation of the VHL tumour suppressor gene in hemangioblastomas of the central nervous system

Abstract: Objectives-Cerebellar haemangioblastoma occurs sporadically or as a component tumour of autosomal dominant von Hippel-Lindau disease. Biallelic inactivation of the VHL tumour suppressor gene, which is located on chromosome 3p, has been shown to be involved in the pathogenesis of both tumour entities. Mechanisms of VHL inactivation are intragenic mutations, mitotic recombination events, and hypermethylation of the promoter region. The systematic and complete examination of these genetic and epigenetic phenomena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 22 publications
3
57
0
4
Order By: Relevance
“…The young age of pheochromocytoma onset indicates the oncogenic dominant function of the VHL gene (Hes et al 2003). Causes of LOH of the VHL gene can be either mutation or methylation of the second allele (Crossey et al 1994, Herman et al 1994, Prowse et al 1997, Glasker et al 2001, Kim & Kaelin 2004. Moreover, recent studies have shown that mutations or methylation of other vulnerable (flanking) genes also affect the VHL phenotype (Martinez et al 2000, Gijtenbeek et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…The young age of pheochromocytoma onset indicates the oncogenic dominant function of the VHL gene (Hes et al 2003). Causes of LOH of the VHL gene can be either mutation or methylation of the second allele (Crossey et al 1994, Herman et al 1994, Prowse et al 1997, Glasker et al 2001, Kim & Kaelin 2004. Moreover, recent studies have shown that mutations or methylation of other vulnerable (flanking) genes also affect the VHL phenotype (Martinez et al 2000, Gijtenbeek et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…Somatic VHL mutations are commonly involved in the tumorigenesis of hemangioblastomas, accounting for up to 50% of sporadic retinal and CNS hemangioblastomas [Maher et al, 1990a;Neumann et al, 1989;Oberstrass et al, 1996;Richard et al, 1998]. Interestingly, sporadic pheochromocytoma are rarely (3%) due to somatic VHL mutations [Bar et al, 1997;Eng et al, 1995;Glasker et al, 2001;Neumann et al, 1993;Sprenger et al, 2001]. However, up to 25% of seemingly sporadic pheochromocytomas actually have a germline VHL, NF-1, c-RET, or SDH mutations.…”
Section: Sporadic Diseasesmentioning
confidence: 99%
“…In line with Knudson's two-hit hypothesis, tumor development requires both an inherited VHL germline mutation in one allele (first hit), present in all the patient's cells, and a somatic loss or inactivation of the wild-type allele (second hit). 31 However, studies of second hit in vHL lesions have so far been based on only a small number of tumors, [32][33][34][35][36] and further studies are needed to elucidate the role the second hit in tumor development.…”
Section: Genotype Influences Rate Of New Tumor Development In Adulthoodmentioning
confidence: 99%